Psikoedukasi: Mengenali Tantrum Pada Anak - Chandra, Sisi Olipia; Fadhli, Muhammad; Juniarly, Amalia (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purposed of this activity is carried out to provide intervention in the form of psicoeducation that counseling to parents who have toddlers. The goal is to increase parental knowledge and awareness regarding parenting patterns that parents have that can affect tantrums in children. This intervention provides information about the definition of tantrums, forms of tantrums, causes of tantrums, impacts of tantrums, how to handle tantrums, and how to prevent tantrums. The service provider hopes that the intervention carried out can help parents to better understand and realize the impacts of improper tantrum handling, so that parents can provide appropriate parenting patterns in handling tantrums. Then based on the results of the pre-test and post-test of the counseling that has been carried out, it was obtained that there was an increase in parental knowledge regarding parenting patterns for tantrums in children.